PENDIDIKAN KARAKTER (Sebuah Usaha Penanaman Kebaikan) - Harjali, Harjalai (IAIN Ponorogo, 2012)
Abstract: Character education plays an important role to build an individuals character. In this notion, since about 2500 years ago Socrates had argued that the fundamental purpose of education is to make someone good and smart. In Islamic history, about 1500 years ago Muhammad, the last Prophet of Islam, also confirmed that the primary mission of educating people is to facilitate the formation of good character in which the ultimate teaching objective is about honesty (al-amien) and how can build such good character is to learn (iqra) from written texts and the passages that are not written. Thousands of years afterwards, the formulation of the main goals of education remain similar, that is to build good personality of learners. Undeniably, school or campus have great influence and impact on the character of students, whether intentionally or not. This fact became the entry point to state that the school or college has a duty and responsibility to make moral education and character building. Furthermore, some experts onÂ educational value, moral or character argue that it is not only a duty or responsibility, but also an effort that should be a priority.